Modalităţi de petrecere a timpului liber pentru tinerii din ţara noastră - Leovaridis, Cristina; Antimiu, Roxana (Calitatea Vieții, 2017)
The presents article focuses on the ways in which young people from Romania spend their free time. In the last decades, a transition from the definition of leisure time as a temporal dimension located outside the time devoted to professional activity and household work to the description of free time from the perspective of human development at an intellectual and spiritual level has taken place. A significant part of this paper is devoted to the classification of the functions of leisure time; factors influencing the forms of spare time, dedicated time; and the ways in which the target spends his free time, through a secondary analysis of statistical data. Qualitative empirical research is based on semi-structured interview guides, applied face-to-face on the one hand to a group of young Romanians aged between 25 and 35, from urban areas, segmented on different civil statutes – unmarried, married, with children and without children, and on the other hand, to some representatives of institutions providing leisure time activities.